Application For College Representative Community Of Allamanda Using Web-Based - Mohamad Afif Syahmi, Mohd Majmi (Universiti Malaysia Sarawak (UNIMAS), 2020)
The selection of new members for the College Representative Community of Allamanda is one of the most important aspects of the college community. The main purpose of the establishment of a college representative committee is to voice the Allamanda college student which population from UNIMAS students to the staff of the college's Allamanda office on issues and welfare within the college. Therefore, it is important to select members of the College Representative Community of Allamanda to lead the activities conducted at your college. The current method used for the application of new members to the College Representative Community of Allamanda is manual. The College Representative Community of Allamanda members still keeps important data, such as the application form on file. This method provides the risk that the probability of being lost during the form preparation process will occur. for this reason, the Web-based college application committee of the Allamanda college has been proposed to upgrade the old system. The system is designed to assist the college's representative college committee to store the necessary data in the system. The system also allows applicants to apply online only. The applicant can review the information and select the desired position. Subsequently, the applicant may also be informed of any announcements and results of the selection of the College Representative Community Of Allamanda committee through the website only.